Treatment of depression in adults with cancer: a systematic review of randomized controlled trials. Issue 5 (19th June 2013) - Walker, J.; Sawhney, A.; Hansen, C. Holm; Ahmed, S.; Martin, P.; Symeonides, S.; Murray, G.; Sharpe, M.
Abstract : Background: Depression is a leading cause of disease burden worldwide and is especially problematic in people with chronic diseases, including cancer. Although depression can be effectively treated in the general population using antidepressant medication and psychological treatments, these treatments may have different benefits and harms in cancer patients. Previous reviews have not adequately addressed this topic. We therefore aimed to determine which, if any, treatments are effective for patients with diagnoses of both cancer and depression. Method: We conducted a systematic review of relevant randomized controlled trials identified through searches of Medline, EMBASE, PsycINFO and The Cochrane Central Register of Controlled Trials (CENTRAL). Results: Seven relatively small trials met the selection criteria. These provided some evidence that antidepressant medication, given alone or in combination with a psychological treatment, may be effective. We found no good evidence for psychological treatments given alone or for any other forms of treatment. Conclusions: There is very limited evidence from clinical trials to guide the treatment of cancer patients with a diagnosis of depression, especially for psychological treatments. High quality trials of treatments for depression in patients with cancer are urgently needed.